Effects of Organizational Support and Organizational Justice on Police Officers’ Work Engagement - Piotrowski, Andrzej; Rawat, Samir; Boe, Ole (Frontiers in Psychology, 2021)
The impact of organizational support and organizational justice on work engagement was investigated in a group of police officers. A review of the literature revealed that studies reporting differences between the influence of supervisors and coworker justice and support on work engagement among police officers are grossly insufficient. This study hypothesized that organizational support and organizational justice would positively predict work engagement among police officers. It was also hypothesized that, among police officers, supervisor support is more strongly related to work engagement than coworker support and that supervisor justice is more strongly linked to work engagement than coworker justice. Participants were 170 police officers who worked in police departments in northern Poland. A regression analysis showed that supervisor support and supervisor justice had a positive effect on police officers’ work engagement, whereby organizational support coupled with organizational justice accounted for 26% of the variability of work engagement. Theoretical and practical implications are discussed, and directions for future research are suggested.